Research on the Harmonic Impedance of Three-phase PWM Converter - SHI Hongtao; ZHUO Fang; HOU Lixiang; YUE Xiaolong; ZHANG Dong; GENG Zhiqing (Kongzhi Yu Xinxi Jishu)
Harmonic impedance is a key parameter used to analyze the stability of system, optimized design of filter, and so forth. It developed an output impedance model in abc coordinates and dq coordinates as an example of a typical three-phase PWM inverter. Output impedance of the inverter was extracted and measured by injecting a current perturbation and the parameter of harmonic impedance was got. Simulation results validate the theoretical analysis.